Deformation Inspection and Safety Assessment Method of Buried Flexible Pipeline in Service. Issue 4 (January 2021) - Xinmin, Zhu; Shaokong, Feng; Tao, Huang; Feng, Shang; Lufei, Yang
Abstract: The working performance of buried flexible pipelines is connected with the pipe- soil interaction; the weak stiffness of backfill leads to large long-term pipeline deformation and even structural failure. Spangler's formula is a theory for macroscopic evaluation of pipeline deformation, which cannot reflect the deformation state of various parts around the pipe from a microscopic view. A large number of engineering practices have shown that when the macro radial deformation of the flexible pipe is not large, it is also possible that the local geometric size of the pipeline may change suddenly in the microscopic view. Combining with a diversion project, a laser scanning and piecewise elliptic curve fitting combined method was proposed to measure the empty pipeline deformation in this paper. The deformation pattern of the flexible pipeline was analysis. And then, the analysis results were verified by the elastic wave test and material test data. Based on the deformation inspections, the internal force and related reliability of pipe structure were calculated. Finally, the structural safety of each pipe was assessed to guide the replacement, repair and reinforcement of pipeline.